Islamic Banking Law Perspective in the Concept of National Law - Muhyidin Muhyidin (Gema Keadilan, 2020)
AbstractThe focus of this article is the perspective of Islamic Banking Law in the concept of national law, both from the institutional aspect, the aspect of business activities. As well as aspects of liquidity management and financial instruments used, both at the level of laws and implementing regulations; and influencing socio-political, cultural and economic factors. Islamic banking law is a new entity in which there is interaction and mutual greeting between Islamic law and national law. In other words, Islamic banking law lies in two areas of law: Islamic law and national law. Sharia banking law, as the name implies, is Islamic law because it is formed on the principles of Islamic law. At the same time, Islamic banking law is also part of national law because it is formed by the competent state institution with the infrastructure and mechanisms that are formally justified. The discussion focuses on the dynamics of the encounter between Islamic law and national law as the elements of its formation. Such efforts can not ignore the factors - factors that influence it, whether political, cultural or economic.